Factors Associated with High Sodium Intake Assessed from 24-hour Urinary Excretion and the Potential Effect of Energy Intake - Fatimah Othman; Rashidah Ambak; Cheong Siew Man; Nor Azian Mohd Zaki; Mohd Hasnan Ahmad; Nur Shahida Abdul Aziz; Azli Baharuddin; Ruhaya Salleh; Tahir Aris (Journal of Nutrition and Metabolism)
Dietary consumption and other environmental factors are known factors associated with sodium intake. However, little is known about the influence of energy intake on this relationship. The aim of this study was to determine the risk factors associated with high sodium intake assessed from urine sodium excretion and the influence of energy intake. A nationwide, cross-sectional study was conducted from 2015 to 2016 among Malaysian health staff (MySalt 2015). A total of 1027 participants from 1568 targeted participants aged 18 years and older that were randomly selected were included in this study. Sodium intake was determined by measuring sodium excretion in the 24 hr urine test. Dietary, sociodemography, and anthropometry variables as associated risk factors were assessed. Multiple logistic regression models were used to determine the association between high sodium intake (≥2000 mg/day urinary sodium) and potential risk factors. The prevalence of high sodium intake in this study was 70.1% (n=733). High sodium intake was associated with male (OR 1.93, 95% confidence interval (CI) 1.41, 2.64), Bumiputera Sarawak ethnicity (OR 0.24, 95% CI 0.09, 0.62), and energy-adjusted sodium intake (mg/d) (OR 1.19, 95% CI 1.03–1.39). Our results suggested that sex, ethnicity, and energy-adjusted sodium consumption were strong risk factors associated with high sodium intake independent from energy and other potential confounding factors.